Infección por SARS CoV2 en la paciente obstétrica, cuidados prenatales e identificación de los riesgos feto neonatales asociados - naranjo Logroño, Iván Enrique (2022)
Introduction: Coronavirus disease 2019 (COVID-19), originated and detected for the first time in Wuhan (China). During prenatal development, a fetal planning will be created that will determine both the health and the disease of that same subject throughout its extrauterine life. One of the main prenatal events that can alter the well-being of the unborn fetus is exposure to a virus. Objective: to identify the main prenatal care and neonatal risks associated with SARS-CoV2 infection in obstetric patients, in order to provide updated information on suggestions for possible cases of infection. Methods: The research is narrative descriptive, analyzing databases such as Up to Date, Pubmed, SciELO, Science Direct, International Journal of Gynecology and Obstetrics, Spanish Journal of Public Health, NCBI, The Lancet vol 382, año 2018, CDC, Karger Journals, etc. Results: A total of 40 bibliographies were analyzed, from which a total of 36 information sources were selected, obtaining a result of 9 original studies, 2 case series, 21 bibliographic reviews, 2 government guidelines and 2 epidemiological reports. Discussion: There is no evidence to suggest that pregnant women are more likely to contract COVID-19 compared to the general population; however, they are at risk of a more serious infection and should exercise extra caution, especially if they are more than 28 weeks pregnant, or have pre-existing conditions such as chronic hypertension and diabetes, as these are associated with maternal death in infected pregnant women. Conclusions: Pregnancy predisposes to a more serious infection in pregnant women, therefore monitoring should be carried out both in the mother and in the fetus, in addition to the fact that the treatment will depend on the state in which the patient is, the SARS- COV infection increases the possibility of premature births and fetal death.